Analysis of radioecological monitoring capabilities for assessing the impact of normalized NPP emissions on agroecosystems - Sergei I. Spiridonov; Rena A. Mikailova; Vladimir K. Kuznetsov (Nuclear Energy and Technology)
The regulations for radioecological monitoring (REM) of agroecosystems in areas surrounding operational nuclear power plants (NPPs) are characterized by a high degree of detail. Obtaining the required empirical data involves significant financial costs. This raises the question: to what extent do monitoring data reflect the impact of NPPs on the agricultural environment? Based on long-term emissions data from the Kursk and Rostov NPPs, the dynamics of radionuclide accumulation in soil originating from NPPs were calculated. It was shown that the concentrations of long-lived 137Cs and 90Sr in soil increase over time during NPP operation by 30–40 times. However, a comparison of the calculations with REM data over many years indicates that the contribution of NPP-derived 137Cs and 90Sr to the specific activity of these radionuclides in soil does not exceed 0.01–0.1%. Thus, REM primarily detects 137Cs and 90Sr of global and Chernobyl origin. Due to the negligible NPP contribution, the spatial distribution of 137Cs within 30-km zones is uniform and follows a lognormal distribution. According to estimates, the activity levels of NPP-derived radionuclides in soil, recommended for REM, are below detection limits. The study concludes that REM guidelines for agroecosystems around NPPs should be optimized. Adjustments may include revising the list of radionuclides analyzed, reducing the types of agricultural products monitored, and increasing the intervals between sampling. The need to focus efforts on developing REM programs for assessing impacts in normal and emergency situations is emphasized.